Towards Implementing Lean Manufacturing in Very Small Businesses in Morocco: Qualitative Exploratory Study - Laila Driouach; Mohamed EL Oumami; Zitouni Beidouri; Khalid Zarbane (International Journal of Supply Chain Management, 2020)
Today, very small businesses (VSBs) play a very important role worldwide due to their great employability and strong presence in the economic fabric. Hence, VSB should introduce an organisation system to improve both quality and productivity continuously. Organizations around the globe are opting for implementing Lean manufacturing to eliminate wastes and increase productivity. This research paper aims to promote lean thinking through studying the readiness of VSBs to adopt the lean manufacturing philosophy. In addition, this study focuses on the application level of lean tools. It also aims to investigate the current level of waste awareness in very small manufacturing industries in Morocco. A survey-based on semi-directive interviews is conducted among 16 very small manufacturing industries stakeholders. The main findings pointed out that lean manufacturing is not yet known by VSB in Morocco. However, managers are willing to adopt any tool that allows improvement, particularly Lean tools. The results show that some Lean tools are already applied in VSB such as autonomous maintenance, preventive maintenance, quality circle, 5S and SMED.